ANALISIS PENGARUH SBDK, INFLASI, NILAI TUKAR DAN DPK TERHADAP PENYALURAN KREDIT INVESTASI PERBANKAN (Studi pada Bank Umum Periode 2011:1 – 2015:7 ) - Kurnia, Silva (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This research purpose to analyze how the influence of prime lending rate, inflation, exchange rate, and third party funds to credit investment on the commercial bank. Data used from secondary data that monthly published by Bank Indonesia. The results is, as partial the credit interest base rate, inflation, and the third party fund has the positive influence, and exchange rate has the negative influence to credit investment from commercial bank. The most dominant variables in influencing the credit investment is third party funds.Keyword: credit investment, prime lending rate, inflation, third party funds